Application of Passive Sonar Technology to Mineral Processing and Oil Sands Applications “If you can measure it, you can manage it.” - Christian O’Keefe; John Viega; Mark Fernald (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
"In this presentation, the SONARtrac™ technology platform will be described. CiDRA's proprietary clamp-on, passive sonar array-based flow meter technology performs two independent measurements – flow rate and fluid characterization. Firstly, the meter provides the volumetric flow rate of the mixture by measuring the speed at which naturally occurring turbulent structures convect with the flow past an axial array of sensors. Secondly, the meter uses similar sonar-based processing techniques and naturally occurring sound in the process fluid to measure entrained air levels. The result is a unique ability to measure the flow rate and entrained air level of most fluids – clean liquids, high solids content slurries, and liquids and slurries with entrained air.Also to be presented is the application of the sonar-based technology platform in a variety of oil sands processes, hydrotransport, and minerals beneficiation applications. In particular, difficult slurry flow measurement and control in the areas of comminution and flotation such as mill discharge, hydrocyclone feed/overflow, final concentrate, thickener discharge, and tailings will be discussed. In addition new real time maintenance free process measurement capability will be presented in the areas of entrained air in slurry, collection zone gas holdup (?g), and slurry velocity profiling. The operational advantages and value of these measurements, even in the presence of scale buildup, will be discussed.INTRODUCTIONFlow measurements in the mineral processing and oil sands industry suffer from the limitations placed by previously available flowmeters including the commonly used instruments such as ultrasonic meters, magmeters, turbine meters, orifice plate meters, vortex flow meters, Coriolis flow meters, and venturi meters. The desire or requirement to make a non-contact measurement that is accurate and robust, and can be performed on practically any type of fluid within practically any type of pipe has driven the creation of a new class of flowmeters. This new class of flowmeter technology utilizes sonar-based processing algorithms and an array of passive sensors to measure not only flow, but also fluid composition."